Jimmy Sue interviewed by Bruce Simpson and Bill Gammage in the Drovers oral history project - Sue, Jimmy, 1928-; Simpson, Bruce (Bruce Forbes), 1923-2019; Gammage, Bill, 1942- (2006)
Jimmy Sue, born at Mount Surprise, Qld. (1928), discusses his family background; childhood; living conditions and domestic chores; his schooling; working in a stock camp; shoeing; sleeper cutting; ringbarking; throwing bulls; branding; mustering; drovers and droving trips; cattle rushes; wages; horse riding and horse riding methods; pack horses; horse riding equipment; treatment of horses; camp life; river crossings; working with Indigenous stockmen; stockmen's injuries; the introduction of motorbikes; fights; rodeo riding and rodeo riding techniques; buck jumpers; retirement; notable horsemen; horse and cattle thieves; the end of WWII; gravesites.
Recorded on June 15, 2006 at Emerald, Qld.
Mode of access: Online.
Timed summary (3 p.) and uncorrected transcript (typescript, 47 leaves)
Keywords: Sue, Jimmy, -- 1928- -- Interviews; Drovers -- Queensland -- Interviews; Droving -- Australia -- Anecdotes; Droving -- Australia -- Biography; Cattle drives -- Queensland -- History